Occupational Health Policies on Risk Assessment in Japan - Seichi Horie (Elsevier, 2010)
Industrial Safety and Health Law (ISH Law) of Japan requires abnormalities identifi ed in evaluations of worker health and working environments are reported to occupational physicians, and employers are advised of measures to ensure appropriate accommodations in working environments and work procedures. Since the 1980s, notions of a risk assessment and occupational safety and health management system were expected to further prevent industrial accidents. In 2005, ISH Law stipulated workplace risk assessment using the wording "employers shall endeavor." Following the amendment, multiple documents and guidelines for risk assessment for different work procedures were developed. They require ISH Laws to be implemented fully and workplaces to plan and execute measures to reduce risks, ranking them from those addressing potential hazards to those requiring workers to wear protective articles. A governmental survey in 2005 found the performance of risk assessment was 20.4% and common reasons for not implementing risk assessments were lack of adequate personnel or knowledge. ISH Law specifi es criminal penalties for both individuals and organizations. Moreover, under the Labor Contract Law promulgated in 2007, employers are obliged to make reasonable efforts to ensure employee health for foreseeable and avoidable risks. Therefore, enterprises neglecting even the non-binding provisions of guidelines are likely to suffer signifi cant business impact if judged to be responsible for industrial accidents or occupational disease. To promote risk assessment, we must strengthen technical, fi nancial, and physical support from public-service organizations, encourage the dissemination of good practices to reduce risks, and consider additional employer incentives, including relaxed mandatory regulations.